2021
DOI: 10.1111/bcp.14824
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist‐led interventions to reduce adverse drug events in older people living in residential aged care facilities: A systematic review

Abstract: Aims We aimed to investigate the efficacy and effectiveness of pharmacist‐led interventions to reduce adverse drug events (ADEs) in older people living in residential aged care facilities (RACFs). Methods We systematically searched MEDLINE via PubMed, Embase, Cochrane Central Register of Controlled Trials and PsycINFO from their inceptions to July 2020. We investigated experimental study designs that employed a control group, or quasi‐experimental studies conducted in RACFs. Results We screened 3826 records an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 77 publications
1
49
0
Order By: Relevance
“…The primary outcome of interest was single and multicomponent interventions that improve anticholinergic prescribing practice or reduce adverse drug events due to the consumption of anticholinergic medications. Single-component intervention consists of only one intervention activity, such as medication review [34]. Multicomponent intervention refers to the combination of various components in a single intervention [35], such as medication review and the provision of education [34].…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome of interest was single and multicomponent interventions that improve anticholinergic prescribing practice or reduce adverse drug events due to the consumption of anticholinergic medications. Single-component intervention consists of only one intervention activity, such as medication review [34]. Multicomponent intervention refers to the combination of various components in a single intervention [35], such as medication review and the provision of education [34].…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Single-component intervention consists of only one intervention activity, such as medication review [34]. Multicomponent intervention refers to the combination of various components in a single intervention [35], such as medication review and the provision of education [34]. All interventions (e.g., medication review, educational detailing visits for physicians, nurses, and aides, pocket-sized educational cards along with clinical vignettes, educational internet site, and detailing session with physicians) performed by any healthcare professional targeting participants of either sex, mean age ≥65 years, and admitted to any healthcare setting were included.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Two reviews indicated that interactive staff education techniques such as academic detailing showed the most promise for optimising prescribing patterns. 16,18 Academic detailing is an educational outreach that involves face-to-face interaction between prescribing physicians and a group of experts. 16 Finally, Alldred et al 11 mentioned clinical coaching and gerontology education for nurses and caregivers as an intervention, but they did not report whether it was effective.…”
Section: Staff Educationmentioning
confidence: 99%
“…Six reviews briefly mentioned the concept, without examining it in any level of depth. 10,11,13,14,16,18 A final issue raised in the literature concerned the theoretical foundations of primary studies. Only three reviews 10,12,24 discussed conceptual and practical issues regarding RACS staff behaviour change.…”
Section: Multicomponent Interventionsmentioning
confidence: 99%
See 1 more Smart Citation